Long-term Results of ABI in Children With Severe Inner Ear Malformations. Issue 7 (August 2016) - Sennaroğlu, Levent; Sennaroğlu, Gonca; Yücel, Esra; Bilginer, Burçak; Atay, Gamze; Bajin, M. Demir; Mocan, Burçe Özgen; Yaralı, Mehmet; Aslan, Filiz; Çınar, Betül Çiçek; Özkan, Burcu; Batuk, Merve Özbal; et al.
Abstract : Objective: To report the long-term outcomes of children who received auditory brainstem implant (ABI) because of severe inner ear malformations. Study Design: Retrospective chart review. Setting: Tertiary referral otolaryngology clinic. Subjects and Methods: Between July 2006 and October 2014, 60 children received ABI at Hacettepe University. Preoperative work up included otolaryngologic examination, audiological assessment, radiological evaluation together with assessment of language development and psychological status. The surgeries were performed via retrosigmoid approach with a pediatric neurosurgeon. Intraoperatively, electrical auditory brainstem response was utilized. Initial stimulation was done 4 to 5 weeks postoperatively. Outcomes were evaluated with Categories of Auditory Performance (CAP), speech intelligibility rate (SIR), functional auditory performance of cochlear implant (FAPCI) and Manchester Spoken Language Development Scale scores; receptive and expressive language ages were determined. Results: Sixty children who received ABI were between ages of 12 and 64 months. Thirty-five patients with follow up period of at least 1 year, were reported in means of long-term audiological and language results. The most prevelant inner ear malformation was cochlear hypoplasia (n = 19). No major complication was encountered. Majority of the patients were in CAP 5 category, which implies that they can understand common phrases without lip reading. SIR was found out to be better with improving hearing thresholds. Children with ABI were performing worse than average cochlear implantation (CI) users when FAPCI scores were compared. Patients with the best hearing thresholds have expressive vocabulary of 50 to 200 words when evaluated with Manchester Spoken Language Development Scale. There was no relationship between the number of active electrodes and hearing thresholds. The type of inner ear anomaly with the best and the worst hearing thresholds were common cavity and cochlear aperture aplasia, respectively. Patients with additional handicaps had worse outcomes. Among 35 children, 29 had closed set discrimination and 12 developed open set discrimination above 50%. It was determined that, progress of the patients is faster in the initial 2 years when compared with further use of ABI. Conclusion: ABI is an acceptable and effective treatment modality for pediatric population with severe inner ear malformations. Bilateral stimulation together with CI and contralateral ABI should be utilized in suitable cases. Abstract : Supplemental Digital Content is available in the text